SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI EVENT DI KOTA AMBON - Dien, Marion Erwin; Parlindungan, Rivaldi Arion (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
Event is a certain agenda, activity or festival that shows, displays and celebrates to commemorate important things that are held at a certain time with the aim of communicating messages to visitors. Ambon City is very thick with culture and art and has been recognized by the world as a world music city. However, people are still unfamiliar with the art movement in Ambon city due to the lack of information about events. Therefore, in this research, a geographic information system application for mapping the location of events in the city of Ambon is made so as to facilitate event visitors in the city of Ambon.